Optimization and Challenges of Implementing Academic Service Management Information Systems in Muhammadiyah Higher Education: A Multiple-Case Study - Wahyu Triono; Kirana Lesmi; Iim Khotimah (Jurnal Pendidikan Islam, 2023)
Purpose – This research aims to analyze the implementation of the Academic Services Management Information System (MIS) at Muhammadiyah Higher Education Institutions (PTM) in Cirebon and Bandung, evaluate its effectiveness in improving the quality of learning, and identify and address challenges in its implementation. Design/methods/approach – The study employs a qualitative approach within an interpretive paradigm, with a multiple-case study design at PTM Cirebon and Bandung during 2022. Primary and secondary data were collected through interviews, observations, and documentation, followed by data analysis, including information reduction and data validation. Findings – The results indicate that the Academic Services MIS at PTM has not been optimally implemented, particularly in planning and information distribution. The main challenges include limited information access and lack of effective coordination. However, the universities have taken strategic steps to address these issues, including efficient budget allocation and utilizing MIS as a learning tool. Research implications – These findings provide important insights for higher education managers in optimizing the use of Academic Services MIS. Implications include enhanced resource allocation, human resources training, and improved coordination and communication systems. The study also suggests the need for more inclusive policy strategies to address resource disparities between institutions.